Efferocytosis and inflammation: a bibliometric and systematic analysis - Cao, Xin; Li, Fen; Xie, Xi; Ling, Guanghui; Tang, Xiaoyu; He, Wenfang; Tian, Jing; Ge, Yan (Frontiers in Medicine, 2025)
ObjectiveTo visualize and analyze the trends and hotspots of efferocytosis and inflammation via bibliometric methods.MethodsRelevant articles and reviews from 2006 to 2023 were retrieved from the Web of Science Core Collection. The data were processed with CiteSpace, and some graphs were generated with Microsoft Excel (version 2016), VOSviewer, Scimago Graphica, Bibliometrix and R Studio.ResultsA total of 1,003 papers were included, revealing a significant upward trend in efferocytosis and inflammation research. The United States (456, 45.46%), China (164, 16.35%) and the United Kingdom (99, 9.87%) were the three countries with the highest numbers of publications. Harvard University (84, 6.74%) contributes the most out of the top 5 institutions. Among the researchers in this field, Serhan CN was the author with the highest number of articles in the field (35, 3.49%), and deCathelineau AM first named “efferocytosis” in 2003. Keyword analysis identified “activation,” “tam receptors,” “docosahexaenoic acid” “systemic lupus erythematosus,” “myocardial infarction” and “alveolar macrophages” as core topics, indicating a concentrated trend in the mechanism of physiological state and inflammatory diseases such as autoimmune, cardiovascular, and pulmonary diseases. The latest surge words “inflammation resolution” and “cancer” in the keyword heatmap indicate future research directions.ConclusionResearch on the association between efferocytosis and inflammation has been a promising field. Key areas of focus include the crucial role of efferocytosis on tissue homeostasis and the pathogenesis of nontumorous inflammatory diseases. Future research will likely continue to explore these frontiers, with an emphasis on understanding efferocytosis in the context of chronic diseases and cancer, as well as developing novel therapeutic strategies.